How do rainfall intensity and raindrop size determine stemflow production? Quantitative evaluation from field rainfall simulation experiments. Issue 13 (3rd October 2021) - Zhang, Yafeng; Wang, Xinping; Pan, Yanxia; Hu, Rui
ABSTRACT: The effects of rainfall intensity on stemflow production as described in the literature are quite inconsistent (increase, decrease, or no clear relationship) due to complex interactions between rainfall characteristics, and the effect of raindrop size on stemflow production has rarely been explored. Here we conducted field rainfall simulation experiments on two dominant xerophytic shrubs ( Caragana korshinskii and Artemisia ordosica ) in northwesten China to quantitatively examine the relationship between rainfall intensity and stemflow production, and to test whether larger raindrops result in a decrease in stemflow production. We found that (1) stemflow production increased with rainfall intensity until reaching a threshold value and then began to decrease, and (2) stemflow showed a significant ( P < .01) linear decrease with increasing raindrop size. Our study is useful to reconcile the disputed relationships between rainfall intensity and stemflow production, and provides a basis for a quantitative evaluation to fill the knowledge gap regarding how raindrop size determines stemflow production.